High-reliability underfill material with good electrical insulativity

By using underfill materials composed of trimellitic anhydride, pyridine, dichloride sulfoxide and other components, the problem of poor protection function of traditional materials during temperature circulation and high temperature and high humidity aging is solved, and the high electrical insulation, high temperature resistance and low temperature resistance and temperature resistance of electronic devices are achieved, which significantly improves the reliability of electronic devices.

CN119798918AActive Publication Date: 2025-04-11YANTAI DARBOND TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411843522.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-14
Publication Date
2025-04-11
Estimated Expiration
2044-12-14

AI Technical Summary

Technical Problem

Traditional underfill materials have poor protection functions for the solder joints of electronic devices during temperature cycling and high temperature and high humidity aging, resulting in low reliability of electronic devices.

Method used

An underfill material consisting of trimellitic anhydride, pyridine, dichloride, dimethylformamide, polypropylene glycol, difunctional anhydride curing agent, diphenol-based methane-type epoxy resin, aminophenol-based trifunctional epoxy resin, toughening agent, silane coupling agent, diluent and latent curing accelerator is used to form a high-performance fill material by combining self-synthetic anhydride curing agent and epoxy resin.

Benefits of technology

This material has good electrical insulation, high and low temperature resistance, and good temperature resistance, which significantly improves the reliability of electronic devices and reduces adverse effects such as short circuits caused by too narrow spacing between solder joints and pins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005188493010000061
    Figure BDA0005188493010000061
Patent Text Reader

Abstract

The invention relates to a high-reliability bottom filling material with good electrical insulating property. The bottom filling material is prepared from the following raw materials in parts by weight: 35-40 parts of a self-synthesized anhydride curing agent, 15-25 parts of diphenol methane type epoxy resin, 15-20 parts of aminophenyl trifunctional group type epoxy resin, 6-12 parts of a toughening agent, 0.5-1 part of a silane coupling agent, 4-7 parts of a diluent and 8-12 parts of a latent curing accelerator. The underfill material disclosed by the invention has the advantages of good electrical insulating property, good high and low temperature resistance, good temperature and humidity resistance and the like, and has obvious advantages compared with a traditional underfill material, so that an electronic device has higher reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-reliability bottom filling material with good electrical insulation, belonging to the field of adhesives. Background Art

[0002] With the improvement of the integration of electronic devices, the size and spacing of device pins are getting smaller and smaller, and higher and higher requirements are put forward for the impact stress and electrical insulation performance of the pin solder joints. The bottom filling technology uses epoxy resin materials filled into the bottom of the device to provide good protection for the device. During the temperature cycle, the device pin solder joints will be subjected to additional stress. The bottom filling material can effectively absorb the stress of the pin solder joints during the temperature cycle. Under the action of high temperature and high humidity, short circuits will occur between the small pitch pin solder joints. The bottom filling material can improve the electrical insulation between the small pitch pin solder joints. Advanced bottom filling technology can meet the increasing reliability requirements of electronic devices.

[0003] The rapid development of bottom filling technology has led to the problem that traditional bottom filling materials have poor protection function for the solder joints of electronic device pins during temperature cycling and high temperature and high humidity aging, which seriously affects the reliability of electronic devices. Summary of the invention

[0004] The bottom filling materials currently on the market generally have the problems of poor electrical insulation and poor reliability. In view of the deficiencies of the prior art, the present invention provides a high-reliability bottom filling material with good electrical insulation. The prepared bottom filling material has the advantages of good electrical insulation, good high and low temperature resistance, good temperature and humidity resistance, etc. Compared with traditional bottom filling materials, it has obvious advantages and enables electronic devices to have higher reliability.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a high-reliability bottom filling material with good electrical insulation:

[0006] a. By mass: 14-15 parts of trimellitic anhydride, 5.5-6.5 parts of pyridine, 22-24 parts of dichlorothionyl, and 0.03-0.06 parts of dimethylformamide are added to a three-necked flask in sequence, and then an equal volume of ethylene dichloride is added as a solvent, a condenser is installed, heated to 55-65°C, a speed of 20RPM is set, mechanical stirring is performed for 0.5-1h, and cooled to room temperature; under the stirring condition, 14-15 parts of pyridine are added dropwise at a uniform speed, and the dropping speed is controlled to drip for 1h; under the stirring condition, 40-45 parts of polypropylene glycol are added dropwise at a uniform speed, and the dropping speed is controlled to drip for 2.5h; the speed is set to 35RPM, mechanical stirring is performed for 1-2h, the mixed solution is poured into a separating funnel, and an equal volume of deionized water is added to the mixed solution, the water layer is removed after shaking, and the remaining liquid is distilled at 80°C under reduced pressure for 1h to obtain a self-synthesized acid anhydride curing agent;

[0007] b. By mass: 35-40 parts of self-synthesized curing agent, 15-25 parts of diphenol methane epoxy resin, 15-20 parts of aminophenol trifunctional epoxy resin, 6-12 parts of toughening agent, 0.5-1 part of silane coupling agent, 4-7 parts of diluent, 8-12 parts of latent curing accelerator are sequentially put into a stirring kettle, set the speed to 35RPM under vacuum -0.098MPa, and stir for 2-3h to obtain the bottom filling material of the present invention.

[0008] Based on the above technical solution, the present invention can also be improved as follows.

[0009] Furthermore, the polypropylene glycol is PPG-400 produced by Hai'an Petrochemical Plant in Jiangsu Province.

[0010] The beneficial effect of adopting the above further scheme is that the terminal hydroxyl groups of the polypropylene glycol molecular chain can generate a synthetic product of trimellitic anhydride structure and pyridine hydrochloride through esterification reaction; effectively increase the flexibility and disorder of the molecular chain, so that the synthetic product remains in a liquid state and has good processability and reactivity.

[0011] Furthermore, the self-synthesized acid anhydride curing agent is a bifunctional acid anhydride curing agent with a viscosity of 800 to 1500 mPa·s and an acid anhydride equivalent of 275 to 295 g / mol.

[0012] The beneficial effect of adopting the above further scheme is that the bifunctional anhydride curing agent with a polyether long-chain molecular structure has better electrical insulation performance, better high and low temperature impact resistance, and better moisture and heat resistance than traditional anhydride curing agents, which is the key core of the present invention.

[0013] Furthermore, the diphenol methane epoxy resin is ZLF-160U produced by Xi'an Zhilun.

[0014] The beneficial effect of adopting the above further scheme is that the diphenol methane type epoxy resin has the characteristics of low viscosity, high reactivity and high adhesion.

[0015] Furthermore, the aminophenol-based trifunctional epoxy resin is 630LSD produced by Shandong Shengquan Electronic Materials Co., Ltd.

[0016] The beneficial effect of adopting the above further scheme is that the aminophenol-based trifunctional epoxy resin can form a higher cross-linking density during the thermal curing process, so that the system has high adhesion, good heat resistance and good electrical insulation performance.

[0017] Furthermore, the toughening agent is a polyurethane modified epoxy resin, preferably EPU-133S produced by Shanghai Luohe High-tech Materials Co., Ltd.

[0018] The beneficial effect of adopting the above further scheme is that the polyurethane-modified epoxy resin forms an interpenetrating polymer network structure with the polyurethane molecular chain segments and the epoxy molecular chain segments, which has a good toughening effect and can improve the toughness and bonding performance of the system.

[0019] Furthermore, the silane coupling agent is epoxytrimethoxysilane, preferably Dynasylan GLYMO produced by Evonik Industries AG of Germany.

[0020] The beneficial effect of adopting the above further scheme is that the epoxy group and the siloxane group in the molecular structure of epoxytrimethoxysilane interact with each other, which is beneficial to improving the wettability of the system to the substrate, and improving the flow filling performance and bonding performance.

[0021] Furthermore, the diluent is diglycidyl tetrahydrophthalate. Preferably, it is XY815 produced by Anhui Xinyuan Technology Co., Ltd.

[0022] The beneficial effect of adopting the above further scheme is that diglycidyl tetrahydrophthalate reduces the viscosity of the system, improves the flow filling performance, and has good low temperature resistance, thereby improving the low temperature adhesion of the system.

[0023] Furthermore, the latent curing accelerator is an aromatic diamine salt, preferably HS-601 produced by Chuzhou Huisheng Electronic Materials Co., Ltd.

[0024] The beneficial effect of adopting the above further scheme is that the liquid aromatic diamine salt has good dispersibility and stability in the system; and has a good promoting effect on the acid anhydride curing agent, which can meet the requirements of the system to reduce the curing temperature and increase the curing speed.

[0025] The beneficial effects of the present invention are as follows: the bottom filling material of the present invention has good electrical insulation, effectively reducing adverse effects such as short circuits caused by too narrow solder joints and pin spacing; has good high and low temperature resistance, effectively absorbing the stress on the pin solder joints during temperature changes to protect them; has good temperature and humidity resistance, and effectively ensures the reliability of electronic devices in actual working environments. DETAILED DESCRIPTION

[0026] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0027] Example 1 Synthesis of Self-synthesized Acid Anhydride Curing Agent An-1

[0028] By mass: 74.23 g of trimellitic anhydride, 30.38 g of pyridine, 114.62 g of dichlorothionyl, and 0.25 g of dimethylformamide were added to a three-necked flask in sequence, and then an equal volume of dichloroethane was added as a solvent. The condenser was installed, heated to 60°C, the speed was set to 20 RPM, mechanically stirred for 1 hour, and cooled to room temperature; under the stirring condition, 73.08 g of pyridine was uniformly added dropwise, and the dropping speed was controlled to be completed within 1 hour; under the stirring condition, 207.69 g of polypropylene glycol PPG-400 was uniformly added dropwise, and the dropping speed was controlled to be completed within 2.5 hours; the speed was set to 35 RPM, mechanically stirred for 2 hours, the mixed solution was poured into a separating funnel, and an equal volume of deionized water was added to the mixed solution. After shaking, the water layer was removed, and the remaining liquid was distilled at 80°C under reduced pressure for 1 hour to obtain a self-synthesized acid anhydride curing agent An-1.

[0029] Example 2, Example 3, Example 4

[0030] According to the formula shown in Table 1, synthetic anhydride curing agent An-1, diphenol methane epoxy resin ZLF-160U, aminophenol trifunctional epoxy resin 630LSD, toughening agent EPU-133S, silane coupling agent GLYMO, diluent XY815, and latent curing accelerator HS-601 were weighed and put into a double planetary stirring kettle in sequence. The speed was set to 35RPM under vacuum conditions of -0.098MPa and stirred for 3h to obtain the bottom filling material.

[0031] Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4

[0032] According to the formula shown in Table 1, synthetic anhydride curing agent An-1, Shin Nippon Rika hexahydrophthalic anhydride curing agent MH700G, American Vantrus dodecenyl succinic anhydride curing agent K-12, diphenol methane type epoxy resin ZLF-160U, aminophenol trifunctional epoxy resin 630LSD, toughening agent EPU-133S, silane coupling agent GLYMO, diluent XY815, and latent curing accelerator HS-601 were weighed and put into a double planetary stirring kettle in sequence, and the speed was set to 35RPM under vacuum conditions of -0.098MPa, and stirred for 3h to obtain the bottom filling material.

[0033] Specific test examples

[0034] The performance of the bottom filling materials of the above-mentioned embodiments 2 to 4 of the present invention and comparative embodiments 1 to 4 was tested by the following experiments. The flow filling property was characterized by viscosity and filling time; the reliability of the electronic device was characterized by the adhesive force value after being subjected to a high and low temperature cycle box and a double 85 aging environment box; and the electrical insulation was characterized by the surface resistivity value of the double 85 aging environment box.

[0035] Test Example 1 Flow and Filling Test

[0036] The viscosity was tested using a Brookfield viscometer with a 42# rotor and a temperature of 25°C, in units of mPa·s. The filling time was tested using a simulated packaged chip with a size of 20 mm×20 mm and a gap of 30 μm, at a temperature of 25°C, in units of s.

[0037] Test Example 2 Electrical insulation test

[0038] The bottom filling material is made into a functional sample and heated and cured at 130°C for 10 minutes. It is then placed in a heat and humidity aging environment box (set temperature 85°C, humidity 85% RH). After a 50V DC power supply is powered on for 500 hours, an insulation resistance tester is used to test the surface insulation resistance of the functional sample after heat and humidity aging, in Ω.

[0039] Experimental Example 3 Reliability Test

[0040] The bottom filling material was made into a PCB bonding sample and heated and cured at 130°C for 10 minutes. It was then placed in a high and low temperature cycle box (set high temperature 70°C, low temperature -25°C) and a damp heat aging environment box (set temperature 85°C, humidity 85% RH) for 168 hours. After being taken out, it was placed at room temperature for 24 hours. The shear strength before and after aging was tested using a universal testing machine, in MPa.

[0041] Table 1 Formula and performance list

[0042]

[0043] As can be seen from the data in Table 1, the bottom filling material of the present invention has the advantages of good electrical insulation, good high and low temperature resistance, good temperature and humidity resistance, etc., and has obvious advantages over traditional bottom filling materials, so that electronic devices have higher reliability. Among them, Comparative Example 1 does not use aminophenol trifunctional epoxy resin 630LSD, the adhesion is reduced, the electrical insulation is poor, and the high and low temperature resistance and temperature and humidity resistance are acceptable; Comparative Example 2 does not use tetrahydrophthalic acid diglycidyl ester XY815, the adhesion is not affected, the electrical insulation is good, the temperature and humidity resistance is good, but the high and low temperature resistance is poor. Comparative Example 3 and Comparative Example 4 do not use the self-synthesized anhydride curing agent of Example 1 in the patent of the present invention, but use commercially available products hexahydrophthalic anhydride MH700G and dodecenyl succinic anhydride K-12; MH700G has acceptable adhesion, but poor electrical insulation and aging resistance; K-12 has acceptable adhesion and high and low temperature resistance, but poor electrical insulation and temperature and humidity resistance.

[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-reliability bottom filling material with good electrical insulation, comprising the following components, by weight, 35-40 parts of a self-synthesized acid anhydride curing agent, 15-25 parts of a diphenol methane epoxy resin, 15-20 parts of an aminophenol trifunctional epoxy resin, 6-12 parts of a toughening agent, 0.5-1 parts of a silane coupling agent, 4-7 parts of a diluent, and 8-12 parts of a latent curing accelerator.

2. A high reliability bottom filling material with good electrical insulation according to claim 1, characterized in that: The preparation steps of the self-synthesized acid anhydride curing agent are as follows: according to the mass parts, 14-15 parts of trimellitic anhydride, 5.5-6.5 parts of pyridine, 22-24 parts of thionyl chloride, and 0.03-0.06 parts of dimethylformamide are added into a three-necked flask in sequence, and then an equal volume of ethylene dichloride is added as a solvent, a condenser is installed, and the mixture is heated to 55-65° C., the rotation speed is set to 20RPM, mechanical stirring is performed for 0.5-1h, and the mixture is cooled to room temperature; under the stirring condition, 14-15 parts of pyridine are added dropwise at a uniform speed, and the dropping speed is controlled to be completed within 1h; under the stirring condition, 40-45 parts of polypropylene glycol are added dropwise at a uniform speed, and the dropping speed is controlled to be completed within 2.5h; the rotation speed is set to 35RPM, and mechanical stirring is performed for 1-2h; the mixed solution is poured into a separating funnel, deionized water of an equal volume to the mixed solution is added, the water layer is removed after being shaken, and the remaining liquid is distilled under reduced pressure at 80° C. for 1h to obtain the self-synthesized acid anhydride curing agent; the reaction formula is as follows: 。 3. A high reliability bottom filling material with good electrical insulation according to claim 2, characterized in that: The polypropylene glycol has a viscosity of 3000-4500 mPa·s, a molecular weight of 360-440, and a hydroxyl value of 255-312 mgKOH / g.

4. A high reliability bottom filling material with good electrical insulation according to claim 2, characterized in that: The self-synthesized acid anhydride curing agent has a viscosity of 800 to 1500 mPa·s and an acid anhydride equivalent of 275 to 295 g / mol.

5. The high reliability bottom filling material with good electrical insulation according to claim 1, characterized in that: The diphenol methane epoxy resin has a viscosity of 1000-1400 mPa·s at 25° C., an epoxy equivalent of 156-165 g / eq, and a total chlorine content of less than 100 ppm.

6. The high reliability bottom filling material with good electrical insulation according to claim 1, characterized in that: The aminophenol-based trifunctional epoxy resin has a viscosity of 500-1000 mPa·s at 25° C., an epoxy equivalent of 95-105 g / eq, and a total chlorine content of less than 750 ppm.

7. A high reliability bottom filling material with good electrical insulation according to claim 1, characterized in that: The toughening agent is polyurethane modified epoxy resin, with a viscosity of 20000-40000 mPa·s at 25° C., an epoxy equivalent of 240-280 g / eq, and a total chlorine content of less than 900 ppm.

8. The high reliability bottom filling material with good electrical insulation according to claim 1, characterized in that: The silane coupling agent is epoxytrimethoxysilane.

9. The high reliability bottom filling material with good electrical insulation according to claim 1, characterized in that: The diluent is diglycidyl tetrahydrophthalate, with a viscosity of 500-1000 mPa·s at 25° C., an epoxy equivalent of 150-180 g / eq, and a total chlorine content of less than 900 ppm.

10. The high reliability bottom filling material with good electrical insulation according to claim 1, characterized in that: The latent curing accelerator is an aromatic diamine salt with a viscosity of 50 to 300 mPa·s at 25° C. and an amine equivalent of 35 to 45 g / mol.

Citation Information

Patent Citations

  • Compound 1, 5-trimellitic anhydride glutarate and compounding method thereof

    CN106543122A

  • Four-degree-of-functionality epoxy resin curing agent and preparation method thereof

    CN109180910A

  • Bottom filling material with good compatibility with soldering flux

    CN115093815A

  • Ester of trimellitic anhydride and process for producing the same

    GB1390716A

  • Curing agent for epoxy resin

    JP1981103216A